Does Integration Occur on a Certain Day? The Case of the Lithuanian Stock Market - Brahmana, Rayenda; Asmar, Muath (Research Gate, 2011)
This paper explores the intersection between market integration and Weekend Effect by investigating the possibility of integration to occur in a certain day over the period of 1 January 1990 until 31 December 2010. The integration was retrieved from the intercept time varying rolling regression of Stehle’s (1977) ICAPM Model. Meanwhile, the Weekend effect is captured by the intercept time varying rolling regression of French’s (1980) Monday Effect Model. For robustness, we modified the French’s Model to examine the seasonality inside market integration with Exchange Rate and Oil Prices as the control variable. This research remarks the seasonality of Lithuanian stock market integration.